Survei jenis bahan cetak gigi tiruan cekat di jakarta - James Handojo; Khalista Salshabilla (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Fixed prosthodontics final impression is heavily influenced by the impression material selection. Purpose: To find out the impression materials used by dentists in for fixed prosthodontics impression in Jakarta. Methods: Descriptive observational research with a cross-sectional design involving 96 respondents. Data collected using a questionnaire distributed to dentists in Jakarta through google form. Results: The usage percentage of polyvinyl siloxane is higher than alginate and polyether for fixed prosthodontics final impression. Conclusion: The percentage of never using alginate impression material was (57%), The very often frequency of using polyvinyl siloxane shows a percentage of (56%). The results of this study indicate that the use of polyvinyl siloxane is more widely used by dentists in Jakarta.